Drawing as a learning tool for anatomy: design and implementation of a method. - Elena Martínez Carracelas; Miguel Ángel Fernández-Villacañas Marín; Matilde Moreno Cascales; Diego Flores Funes (Revista Española de Educación Médica)
Anatomy is fundamental in Medical Education. This study evaluates a method of learning skull anatomy and improving three-dimensional comprehension through systematic drawings. A quasi-experimental study was carried out with 67 volunteer first-year medical students to evaluate the influence of using a drawing method during classes to improve the level of anatomical knowledge and three-dimensional understanding. Students attended a four-sessions drawing workshop to work on the four basic anatomical views of the skull. In each session they made one free drawing and another one following the method, both being evaluated checking the presence of 25 predefined anatomical items. Their progress was assessed by comparing the scores obtained at the beginning and at the end of the workshop with the Wilcoxon signed-rank test. Likewise, the mean scores of the subject General Anatomy of the Locomotor System of the participants in the workshop and the rest of the students who did not participate were compared with the Mann-Whitney U test. Finally, students evaluated the activity through a satisfaction survey. An increase in drawing scores was observed. The first drawing of the first session scored with a median of 8/25 ±4.0, being 11/25 ± 5.0 (p=0.00) the first drawing score of the fourth session. The second drawing scores in the objective correction were 23/25 ±4 and 25/25 ±1 in the first and fourth sessions, respectively (p=0.00). Statistically significant differences were found between the two groups. The workshop participating students obtained better grades in all final exams (theoretical and practical exams). The experience was rated very positively. This study concludes that the learning method had a positive influence on the learning of Anatomy and that attending the workshop improved the level of knowledge, the ability to discriminate details and skull the three-dimensional understanding.